2021
DOI: 10.1039/d0nr08640a
|View full text |Cite
|
Sign up to set email alerts
|

Tunable and transparent broadband metamaterial absorber with water-based substrate for optical window applications

Abstract: A tunable and transparent metamaterial absorber (MMA) with a water-based substrate is presented, with high optical transparency and broadband microwave absorptivity. In the material structure, indium–tin–oxide (ITO) films are included...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 52 publications
0
32
0
Order By: Relevance
“…In addition to the change in inherent properties, the thickness of dielectric spacer can also be adjusted to design MAs with tunable absorption because of the enhanced near-field coupling between the periodic patterns and metallic ground with lower distance. [225] Zhang et al proposed a mechanically stretchable MA. [226] By applying a strain along H field direction, the resonant frequency was dynamically moved from 11.15 to 11.56 GHz.…”
Section: Tailoring Thicknessmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the change in inherent properties, the thickness of dielectric spacer can also be adjusted to design MAs with tunable absorption because of the enhanced near-field coupling between the periodic patterns and metallic ground with lower distance. [225] Zhang et al proposed a mechanically stretchable MA. [226] By applying a strain along H field direction, the resonant frequency was dynamically moved from 11.15 to 11.56 GHz.…”
Section: Tailoring Thicknessmentioning
confidence: 99%
“…Instead of using air as tunable element, Zhang et al proposed a tunable MA utilizing water substrate. [225] By adjusting the thickness of the water layer from 0 to 1.2 mm via two syringes, the absorption was tuned from narrow band to broad band in the frequency range of 5.8-16.2 GHz. Note that all aforementioned MAs are operating at microwave range, which are relatively easy in fabrication due to the centimeter size.…”
Section: Tailoring Thicknessmentioning
confidence: 99%
“…32 Zhang et al demonstrated an actively tunable MMA with a water-based substrate, polymethyl methacrylate (PMMA), distilled water and ITO lms, achieving absorbance over 90% within 5.8-16.2 GHz, and 70.18% optical transmittance. 33 Other design schemes, including multilayer transparent resistive lm and aluminum wire grids, which has great advantages in working bandwidth, but the multilayer structure inevitably reduces the overall transmittance of the absorber. 26,34,35 The absorption bandwidth of aluminum wire grids transparent absorber is limited for its operating bandwidth strongly depends on the structure of the composite resonance.…”
Section: Introductionmentioning
confidence: 99%
“…A metamaterial terahertz biosensor, which has two resonant absorption frequencies, was represented by Li [18] for fast and label-free identification of early-stage cervical cancerous tissues. Seeking for the low-frequency band gap, metamaterials with different microstructure were designed and presented by Zhang [19] and Lin [20], respectively. In these works, it could be noted that the nonlinear factors were not taken into consideration.…”
Section: Introductionmentioning
confidence: 99%